1995
DOI: 10.1159/000288958
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Group Intervention and the Rate of Decline of Immunological Parameters in Asymptomatic HIV-lnfected Homosexual Men

Abstract: The aim of the study was to determine changes in the rate of decline of immunological parameters after psychosocial group intervention. Subjects were 26 asymptomatic HIV-infected homosexual men who participated in a cognitive-behavioral group therapy (CBT; n = 14), or an experiential group therapy program (ET; n = 12), both of 15 weeks duration. The outcome measures were changes in the decline of CD4 cell counts, and T cell proliferative responses to anti-CD 3 monoclonal antibodies from preintervention to 24 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 16 publications
(26 reference statements)
0
33
0
Order By: Relevance
“…However, most programs used multiple sessions (range=6-20 sessions; mode= 10 sessions) that were between an hour and two and a half hours in length (mode= 2-h session). Three interventions also supplemented multiple sessions with an additional daylong retreat [25,29,30,32,33]. Only one treatment incorporated booster sessions after the intervention was completed [29,30].…”
Section: Delivery Format Intervention Components Study Designs Trementioning
confidence: 99%
See 3 more Smart Citations
“…However, most programs used multiple sessions (range=6-20 sessions; mode= 10 sessions) that were between an hour and two and a half hours in length (mode= 2-h session). Three interventions also supplemented multiple sessions with an additional daylong retreat [25,29,30,32,33]. Only one treatment incorporated booster sessions after the intervention was completed [29,30].…”
Section: Delivery Format Intervention Components Study Designs Trementioning
confidence: 99%
“…Additionally, the majority of HIV-infected individuals included in the reviewed interventions were Caucasian. While most studies were conducted in the USA, three interventions were conducted with international patient samples [32,33,35,38].…”
Section: Delivery Format Intervention Components Study Designs Trementioning
confidence: 99%
See 2 more Smart Citations
“…As Ironson and colleagues (2002) note in their review, stress management interventions tend to improve psychosocial outcomes but the effects on immune functioning have been inconsistent. For example, some investigators have found improvements in immunological markers such as CD4+ counts for intervention but not control participants (Antoni et al, 1991) whereas other investigators have found similar increases in CD4+ counts for both the intervention and control groups (Mulder et al, 1995). In addition, the association between stressful life events and CD4+ counts among people with HIV tends to be delayed.…”
mentioning
confidence: 99%